An indirect method of imaging the Stokes parameters of a submicron particle with sub-diffraction scattering. (July 2018) - Ullah, Kaleem; Garcia-Camara, Braulio; Habib, Muhammad; Yadav, N.P.; Liu, Xuefeng
Highlights: Scattering distribution of a submicron Cu2 O particle in terms of Stokes parameters has been imaged using a far field parametric microscopic technique. A comparison of this sub-diffraction scattering with the classical Stokes parameters measurement method is included to show the relevant differences and the strength of this technique. The sub-diffraction mapping of scattering signals delivered by our method in terms of Stokes parameters has been verified with finite difference time domain (FDTD) method. Abstract: In this work, we report an indirect way to image the Stokes parameters of a sample under test (SUT) with sub-diffraction scattering information. We apply our previously reported technique called parametric indirect microscopic imaging (PIMI) based on a fitting and filtration process to measure the Stokes parameters of a submicron particle. A comparison with a classical Stokes measurement is also shown. By modulating the incident field in a precise way, fitting and filtration process at each pixel of the detector in PIMI make us enable to resolve and sense the scattering information of SUT and map them in terms of the Stokes parameters. We believe that our finding can be very useful in fields like singular optics, optical nanoantenna, biomedicine and much more. The spatial signature of the Stokes parameters given by our method has been confirmed with finite difference time domain (FDTD) method.